Paleopatologia - rozwój, osiągnięcia i zamierzenia - Gładykowska-Rzeczycka, Judyta Julia (Polskie Towarzystwo Antropologiczne, 1993)
PALEOPATHOLOGY - DEVELOPMENT, ACHIEVEMENTS AND PURPOSE. All these problems are here presented in a very short view.
PALEOPATHOLOGY - DEVELOPMENT, ACHIEVEMENTS AND PURPOSE